2023
DOI: 10.1126/science.adf6249
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the cellular determinants of targeted membrane protein degradation by lysosome-targeting chimeras

Green Ahn,
Nicholas M. Riley,
Roarke A. Kamber
et al.

Abstract: Targeted protein degradation can provide advantages over inhibition approaches in the development of therapeutic strategies. Lysosome-targeting chimeras (LYTACs) harness receptors, such as the cation-independent mannose 6–phosphate receptor (CI-M6PR), to direct extracellular proteins to lysosomes. In this work, we used a genome-wide CRISPR knockout approach to identify modulators of LYTAC-mediated membrane protein degradation in human cells. We found that disrupting retromer genes improved target degradation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 75 publications
0
15
0
1
Order By: Relevance
“…Three branches and T10 were discovered as the optimal components in the DNA dendron, and the linker property might also affect DENTAC performance. In addition, cellular factors determining recycling of extracellular protein degraders and lysosomal maturation also deserve in-depth investigations in the future . We validated the anticancer application of DENTAC by targeting oncogenic MMP-9.…”
Section: Discussionmentioning
confidence: 84%
“…Three branches and T10 were discovered as the optimal components in the DNA dendron, and the linker property might also affect DENTAC performance. In addition, cellular factors determining recycling of extracellular protein degraders and lysosomal maturation also deserve in-depth investigations in the future . We validated the anticancer application of DENTAC by targeting oncogenic MMP-9.…”
Section: Discussionmentioning
confidence: 84%
“…Blockage of M6P biosynthesis genes (e.g., ALGO12, GNPTAB) upregulated the ratio of unoccupied receptors, increasing LYTAC-receptor internalization and the degradation of cell surface proteins, including EGFR and c-Met. 1 Overall, this work discovered a series of critical cellular regulators that modulated LYTAC-mediated degradation of EGFR and c-Met (Figure 1B, right), giving important support for understanding LYTAC mechanism and developing nextgeneration LYTAC with improved clinical potential.…”
mentioning
confidence: 71%
“…Recently, the group of Prof. Carolyn Bertozzi, a laureate of the Nobel Prize in chemistry 2022, reported the detailed mechanism of lysosome-targeting chimera (LY-TAC) in the journal of Science, 1 after the publication of their first LYTAC molecule in Nature in 2020. 2 The establishment of LYTAC, a subtype of targeted protein degradation technology, expands the scope of protein degradation to extracellular and membrane-associated targets, and Bertozzi group's new discovery is expected to accelerate the development of LYTAC in cancer therapy.…”
mentioning
confidence: 99%
“…50 Using CRISPR/Cas9-knockout screening, it was found that IGF2R (insulin like growth factor 2 receptor, an alternative gene name for CI-M6PR ) and several genes involved in protein neddylation and activation of the E3 ligase cullin-3 ( CUL3 ) are essential for the cargo uptake and LYTAC recycling. 115 These results provided not only an unbiased validation of the underlying molecular mechanism of LYTACs but also a potential indicator ( e.g. , neddylation of CUL3) to predict whether and to what extent LYTAC therapy will be effective in vivo .…”
Section: Targeted Degradation Of Secreted and Membrane Proteins Throu...mentioning
confidence: 88%